2020
DOI: 10.1101/2020.10.08.332494
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Common host variation drives malaria parasite fitness in healthy human red cells

Abstract: SUMMARYThe replication of Plasmodium falciparum malaria parasites within red blood cells (RBCs) causes severe disease in humans, especially in Africa. The influence of host erythrocyte variation on parasite replication is largely uncharted, aside from a handful of deleterious alleles like sickle cell. Here, we integrated analyses of exome sequencing, RBC phenotyping, and parasite fitness assays on blood donated by 122 individuals, most with African ancestry. In donors lacking alleles for hemoglobinopathies or … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…For instance, in mice vaccinated with erythrocyte ghosts isolated from P. chaubaudi -infected erythrocytes, RHAG , SPTA1 , KLF1 , and SLC4A1 were among the erythropoiesis-involved genes that were significantly upregulated in response to infection with blood stage Plasmodium chabaudi (Delic et al, 2020). Furthermore, variation in SPTA1 , which encodes a component of the RBC plasma membrane, was recently found to impact P. falciparum growth in cultured human RBCs (Ebel et al, 2020). Lastly, heterozygous deletion in SLC4A1 causes South Asian hereditary ovalocytosis, which confers protection in humans against many Plasmodium species (Jarolim et al, 1991; Paquette et al, 2015), and this gene has been found to be under differential selection pressure in other primate species (Steiper et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in mice vaccinated with erythrocyte ghosts isolated from P. chaubaudi -infected erythrocytes, RHAG , SPTA1 , KLF1 , and SLC4A1 were among the erythropoiesis-involved genes that were significantly upregulated in response to infection with blood stage Plasmodium chabaudi (Delic et al, 2020). Furthermore, variation in SPTA1 , which encodes a component of the RBC plasma membrane, was recently found to impact P. falciparum growth in cultured human RBCs (Ebel et al, 2020). Lastly, heterozygous deletion in SLC4A1 causes South Asian hereditary ovalocytosis, which confers protection in humans against many Plasmodium species (Jarolim et al, 1991; Paquette et al, 2015), and this gene has been found to be under differential selection pressure in other primate species (Steiper et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…HBSS contains salts at the same concentration as RPMI 1640, but lacks amino acids and trace elements found in RPMI. Red blood cells from different donors may have a large influence on P. falciparum growth rates (32): we therefore used a single donor (O+) for all experiments.…”
Section: Methodsmentioning
confidence: 99%